Sunset homeowner's guide to solar heating and cooling - Sunset Books (Menlo Park, California Lane Publishing Co., 1978)
In a clear, nontechnical language, this book explains how solar heating works and how it can be applied to your home - in active and passive space heating, domestic water heating, and pool heating.
"Active & passisve systems, hot water heaters, Pools, Spas ^ tubs."--Cover.
Includes bibliographical references and index.
Keywords: Solar heating; Solar houses